Mechanical characterization of reconstituted leather through the tension and yield test (Nexo Revista Científica, 2022)
The combination of different qualities of leather waste with different polymers and the resulting mechanical properties are potentially important for obtaining new materials. In this study, experiments combining leather chip residue, vinnapas ®400 resin and distilled water produced a new composite material with interesting mechanical properties. In the elaboration, the pH of the leather chip, chip size, resin temperature, softening temperature, pressure and the pressing time exerted on the reconstituted leather plate were controlled. Using fractional factorial design, the influence of the selected independent variables was determined: chip size, chip/resin ratio, percentage of water, resin temperature, pressure and pressing time on the mechanical properties of the composite material. The experimental results showed that there was a main effect of the Chip/Resin ratio variable at its minimum value on the maximum traction effort, reaching a value of 2,657 MPa. Additionally, in the mechanical creep test, it was found that the composite material called reconstituted leather shows a viscoelastic behavior, which resembles the behavior of tanned leather.